Heart Failure with Transient Left Bundle Branch Block in the Setting of Left Coronary Fistula - Stephen P. Juraschek; Lara C. Kovell; Ryan E. Childers; Grant V. Chow; Glenn A. Hirsch (Cardiology Research and Practice, 2011)
Coronary arterial fistulas are rare communications between vessels or chambers of the heart. Although cardiac symptoms associated with fistulas are well described, fistulas are seldom considered in the differential diagnosis of acute myocardial ischemia. We describe the case of a 64-year-old man who presented with left shoulder pain, signs of heart failure, and a new left bundle branch block (LBBB). Cardiac catheterization revealed a small left anterior descending (LAD)-to-pulmonary artery (PA) fistula. Diuresis led to subjective improvement of the patient's symptoms and within several days the LBBB resolved. We hypothesize that the coronary fistula in this patient contributed to transient ischemia of the LAD territory through a coronary steal mechanism. We elected to observe rather than repair the fistula, as his symptoms and ECG changes resolved with treatment of his heart failure.